(untitled) (Al-Qamar, 2021)
Muslims had interaction with Jews since the beginning of Islam and their dialogue with them was usually verbal. It was long after prophetic Era when Muslims started taking interest in reading Jewish scriptures and writing about them. The prime reason behind abstaining from Old Testament was the doctrine of interpolation claimed by Quran. When scholars started taking Old Testament into consideration, their idea of interpolation fluctuated in various ways. The admitted that the interpolation took place in Old Testament but some of them did not agreed upon textual interpolation; rather they claimed that only hermeneutical interpolation was done and text is all safe and authentic. Beside them, another class of Muslim scholars strictly refuted this opinion and they came with the hardcore stance of Tehreef by claiming that the whole of Old Testament has been distorted by Jew Rabbis. This difference of opinion has been analyzed in this article in the light of early Muslim writings about Jews and Old Testament.